Solve for \( f \) \[ 8+5 f=-4 f+1+8 f \] \( f=\square \) Submit
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
To solve the equation \( 8 + 5f = -4f + 1 + 8f \), we begin by simplifying the right side. Combine like terms on the right: \[ -4f + 8f = 4f \] Now the equation becomes: \[ 8 + 5f = 1 + 4f \] Next, we isolate \( f \) by getting all the terms involving \( f \) on one side and the constants on the other. Subtract \( 4f \) from both sides: \[ 8 + 5f - 4f = 1 \] This simplifies to: \[ 8 + f = 1 \] Now, we isolate \( f \) by subtracting 8 from both sides: \[ f = 1 - 8 \] \[ f = -7 \] Thus, the solution is: \( f = -7 \)